A laboratory Study On The Effect Of Temperature And pH On The Stability Of Tilmicosin - Al-Ani, Lubna Ahmed (The Iraqi Journal of Veterinary Medicine, 2007)
The effect of temperature and pH on the stability of the antibacterial“tilmicosin” was evaluated in this study. The temperature degrees studied were25 , 45 and 65 oC each for 24 hours , while the pH values studied were 6 , 7 and8 each at room temperature and for 24 hours also.A microbiological assay method was employed for analysis of the collectedsamples.The results of analysis indicate significant drop in activity of the drug as aresults of exposure to temperature or pH.The above mentioned results necessitate the maintenance of drinking water inthe storage depots of the field below 65 oC especially in summer season, so tokeep the chemical structure of the drug and to offer enough therapeuticconcentration to reach the tissue.